Error Analysis In Oral Production Made By English Department Students In Microteaching Class At Muhammadiyah University Of Surakarta - SAADAH, NAILIS, Prof. Dr. Endang Fauziati, M. Hum (2016)
The objectives of this study are to describe tjhe types of error, to describe the frequency of error, to describe the dominant error, and to explain the sources of error. The type of this study is descriptive qualitative research. The data of this research are utterances containing errors taken from Microteaching video at Muhammadiyah University of Surakarta. The data collection of this research is documentary study. There are 595 utterances containing error. The writer uses descriptive qualitative technique to analyze the data. The witer uses theory from Clark and Clark to analyze the error. In the result of this study, the writer divided types of error into three classification. They are speech error, morphological error, and syntactical error. The writer found 501 utterancer or 84,63% of speech error, 29 utterances or 4,90% of morphological error, and 62 utterances or 10,47% of syntactical error. In speech error, the writer finds 215 utterances containing silent pause or 36,13% of silent pause, 97 utterances containing filled pause or 16,40% of filled pause, 109 utterances containing repeats or 18,32% of repeats, 25 utterances containing stutters or 4,20% of stutters, 2 utterances containing correction or 0,34% of correction, 10 utterances containing interjection or 1,68 of interjection, 6 utterances containing unretraced false starts or 1,01% of unretraced false starts, and 37 utterances containing retraced false starts or 6,22% of unretraced false starts. In morphological error, the writer finds 5 utterances containing vocabulary errors or 0,84% of vocabulary errors, and then 27 utterances containing error in the selection words or 4,54% of error in selection words. And in syntactical error, the wroiter finds 13 utterances containing omission of bound morpheme or 2,18% of bound morpheme, 4 utterances containing addition of bound morpheme or 0,67% of addition of bound morpheme, 34 utterances containing omission of to be or 5,72% of omission of to be, and 11 utterances containing addition of to be or 1,85% of addition of to be.